Multi-locus sequence analysis unveils a novel genus of filarial nematodes associated with ticks in French Guiana - Bruley Marjorie; Duron Olivier (Parasite, 2024)
Filarial nematodes of the Dipetalonema lineage include tick-borne filarioids that infect both domestic and wild vertebrate hosts, but they remain understudied in many cases. In this study, we conducted a molecular characterization of a Dipetalonema-like filarioid (DLF) recently identified in two tick species in French Guiana, South America. While the cox1 mitochondrial gene was the sole marker initially sequenced for describing DLF, its classification and phylogenetic relationship with other members of the Dipetalonema lineage were unclear. Therefore, we better characterized DLF through the sequencing of six additional gene markers and conducted phylogenetic analyses. Based on this multi-locus typing scheme, DLF exhibited significant divergence from known genera and species of filarioids, or other sequences available in public databases, suggesting its potential classification as a novel genus within the Dipetalonema lineage. Phylogenetic analyses further unveiled a close evolutionary relationship between DLF and all other filarioids associated with Acari (ticks and mites) within a robust monophyletic subclade in the Dipetalonema lineage. Overall, these findings confirm the existence of a specialized, Acari-borne group of filarioids and underscore the need for comprehensive investigations into their epidemiology and potential impact on animal health.